Correlation Between Broken Home And Coping Strategy Upon Adolescent Personality - Aji Bayu Utomo; Anna Miftakhul Rizky; Sindi Febriani; Kharisma Rizki Amalia; Erna Erawati (Poltekkes Kemenkes Semarang, 2019)
Background: Youth from broken home families are very vulnerable because of depression experienced in facing stressful conditions. Each individual will develop a stress management strategy called coping strategy, which have impact on ones personality.Objective: To obtain empirical data in order to find out the correlation between broken home and coping strategy in adolescentsMethod: Thestudy used correlational techniques, data collection in the form of a strategyways of coping coping questionnaire from Lazarus and questionnaire identification of broken family. Data analysis using statistics.Results:From the statistical results using the Chi-squared contingency coefficient obtained of 10.615 and C of 0.458. Because the ratio of values C = 0.458 and Cmax = 0.707, based on the norms of contingency shows a sufficient degree of correlation between broken home with coping strategy in Youth Personality at Marsudi Putra Antasena Social Assistance Magelang.Conclusion:There is a significant correlation between youth age personality Broken home with Coping Strategy in adolescents at Marsudi Putra Antasena Social Assistance Magelang, with moderate levels of correlation